Coronaviruses With Special Emphasis on First Insights Concerning SARS 2005
DOI: 10.1007/3-7643-7339-3_3
|View full text |Cite
|
Sign up to set email alerts
|

Severe acute respiratory syndrome: clinical features

Abstract: Chest radiography can serve as a screening tool in the correct clinical setting. In a prospective study conducted in a SARS screening clinic for hospital staff, patients and their relatives, chest radiological changes were

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2005
2005
2005
2005

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…Though a satisfactory serum inhibitory concentration of lopinavir may not be achieved with the oral LPV/r combination [28], a sufficient level may be reached at the intestinal mucosa, since 20% of the drug is found excreted unchanged in the stool [29]. This is significant because severe watery diarrhea is a marked feature in 20.4-76.0% of SARS patients [12,25,30,31] and the gastrointestinal mucosa could be an important reservoir for viral replication and fecal-oral transmission [32]. In an open trial of the use of the LPV/r combination together with ribavirin in 41 patients compared with 111 historical controls, it was shown that patients in the LPV/r group had fewer 21-day adverse clinical outcomes (death/acute respiratory distress syndrome) and their disease course was milder with regard to diarrhea, fever recurrence, and worsening of chest radiographs.…”
Section: Antiviral Agentsmentioning
confidence: 99%
“…Though a satisfactory serum inhibitory concentration of lopinavir may not be achieved with the oral LPV/r combination [28], a sufficient level may be reached at the intestinal mucosa, since 20% of the drug is found excreted unchanged in the stool [29]. This is significant because severe watery diarrhea is a marked feature in 20.4-76.0% of SARS patients [12,25,30,31] and the gastrointestinal mucosa could be an important reservoir for viral replication and fecal-oral transmission [32]. In an open trial of the use of the LPV/r combination together with ribavirin in 41 patients compared with 111 historical controls, it was shown that patients in the LPV/r group had fewer 21-day adverse clinical outcomes (death/acute respiratory distress syndrome) and their disease course was milder with regard to diarrhea, fever recurrence, and worsening of chest radiographs.…”
Section: Antiviral Agentsmentioning
confidence: 99%